Study of mid and long term outcome of hip fracture in elderly operated within 48 hours versus conservative management - Marshall, Delis S.; Ch’ng, Alan S. W.; Looi, Irene (International Journal of Research in Orthopaedics, 2021)
Background: Hip fractures are commonly associated with high morbidities and mortalities. This study aimed to determine post-hip fracture outcomes and survival among patients who underwent operation within 48 hours of fracture diagnosis and among those being treated conservatively. Methods: This retrospective cohort study was conducted at the Hospital Seberang Jaya among patients diagnosed with hip fracture from January to December 2016; confirmed clinical and radiological method. Descriptive analysis was conducted using Statistical package for social sciences (SPSS) version 23. Results: The mean (SD) age of the 61 operated patients was 74 (7.7) years and for the 19 conservatively managed patients 79 (8.0) years. At 12 months, 30 (37.5%) of operated ones, required assisted mobility compared to 8 (10%) of conservatively managed patients. Other outcomes comparable between operated and conservative patients at 12 months post-intervention include: ability to feed on own 46 (57.5%) versus 7 (8.8%), able to dress on own, 45 (56.3%) versus 6 (7.5%); able to bathe on own; 43 (53.8%) versus 2 (2.5%), and independently attending to own toilet needs 44 (55.0%) versus 1 (1.3%). Our study revealed, overall survival were comparatively better among those operated to conservative at 12 months; 52 (85%) versus 9 (47.4%). The mortality at 12 months in the conservative group is much higher than operative group. Conclusions: Ambulatory mobility and survival are significantly better at 12 months post-fracture among the operated patients. Hip fracture must be treated as an emergency and its surgical management given priority.